Detection of bovine herpesvirus 1 in cumulus-oocyte complexes of cows. (October 2018) - Queiroz-Castro, Vanessa L.D.; da Costa, Eduardo P.; Alves, Saullo Vinicius P.; Júnior, Abelardo Silva; Machado-Neves, Mariana; Guimarães, José D.
Abstract: Bovine herpesvirus 1 (BoHV-1) is the causative agent of infectious bovine rhinotracheitis (IBR) and is also associated with reproductive failure. This study investigated the presence of BoHV-1 in cumulus-oocyte complexes (COCs) of naturally-infected cows without clinical signs of IBR. The presence of BoHV-1 in COCs was evaluated by immunofluorescence using confocal laser scanning microscopy. Blood samples and ovaries from 82 cows that had not been vaccinated against BoHV-1 were collected for serological analysis. COCs were divided into two pools: COCs derivate from seropositive cows and from seronegative cows. Then, the samples were processed for confocal microscopy analysis. The results indicated that 61% (50/82) of cows were seropositive for BoHV-1. A total of 719 COCs were obtained from the cows and processed. None of 276 COCs from the 32 seronegative cows presented BoHV-1. However, BoHV-1 was present in the cytoplasm of cumulus cells from 158 out of 443 COCs aspirated from the seropositive cows. The detection of BoHV-1 in the COCs of seropositive cows suggests that the COCs of naturally-infected, asymptomatic cows may be infected with BoHV-1. Graphical abstract: Highlights: Cumulus-oocyte complexes (COCs) from asymptomatic cows presented the BoHV-1. The virus may be present in cumulus cell of COCs. BoHV-1 was detected in the cytoplasm of cumulus cells. Infected COCs could elucidate the reproductive failures shown in seropositive cows.